Antifungal activity of hair tonic extract from straw mushroom (Volvariella volvacea) against the growth of Malassezia furfur - Ajeng Pramesti Cahyani; Retni S Budiarti; Raissa Mataniari; Pinta Murni; Dara Mutiara Aswan; Harlis Harlis (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2026)
Malassezia furfur (M. furfur) is one of several types of fungi that can cause the scalp to experience flaking, known as dandruff. Dandruff can be eliminated using anti-dandruff agents available on the market. In addition, there are natural ingredients that can act as antifungal agents against the fungus that causes dandruff. The straw mushroom (Volvariella volvacea) is one such fungus that contains secondary metabolites such as saponins, tannins, flavonoids, and alkaloids, which function as antifungal agents. This study was quantitative research using an experimental method and a completely randomized design (CRD), consisting of 6 treatments and 4 replicates in the form of positive control, negative control, and straw mushroom extract hair tonic with concentrations of 10%, 30%, 50%, and 70%. The parameters observed were the diameter of the inhibition zone, which indicated antifungal activity, and the evaluation of the hair tonic preparations (pH test, organoleptic test, skin irritation test, and viscosity test). The results of the study showed that the mushroom extract hair tonic had antifungal activity in inhibiting the growth of M. furfur. Based on the DNMRT test analysis, P0 (positive control) was significantly different from P1 (negative control) and the other treatments (P2, P3, P4, P5). This study concluded that there is activity in the hair tonic extract of straw mushrooms in inhibiting the growth of M. furfur, with the best concentration being 30%.